AUTOGENOUS DENTAL TRANSPLANT - LITERATURE REVIEW (International Seven Journal of Multidisciplinary, 2025)
Dental transplantation is an oral rehabilitation option for individuals who have suffered early loss of natural teeth due to trauma or various diseases. In young patients, in addition to not having indications for implants because they have not completed their craniofacial development, the common options offered in dental offices, such as fixed or partial removable prostheses, are also expensive and difficult to access socioeconomically. Because the third molar has a late development and is often indicated for extraction, it is the best option for transplantation. When healthy, it is transplanted into the alveolus where the loss occurred. This can be done in one or two stages and with the use of postoperative retention to better adapt the tooth to the alveolus. Given the above, the present study aims to conduct a literature review on autogenous dental transplantation as a treatment option for patients who have suffered early loss of a dental organ. The research was conducted through websites such as Google Scholar, Scielo, and PubMed with content available from 2008 to 2022. It is concluded that transplantation is a low-cost oral rehabilitation option, thus avoiding the wear of adjacent teeth for the use of fixed prostheses. Patient cooperation is extremely important for the success of autologous dental transplantation.